The hundred secret senses - Tan, Amy. (New York : G.P. Putnam's Sons, 1995)
The Hundred Secret Senses is an exultant novel about China and America, love and loyalty, the identities we invent and the true selves we discover along the way. Olivia Laguni is half-Chinese, but typically American in her uneasiness with her patchwork family. And no one in Olivia's family is more embarrassing to her than her half- sister, Kwan Li. For Kwan speaks mangled English, is cheerfully deaf to Olivia's sarcasm, and sees the dead with her "yin eyes."
Keywords: Chinese American women -- Fiction; Chinese American families -- Fiction; Chinese Americans -- California -- San Francisco -- Fiction; Sisters -- United States -- Fiction; Sisters -- Fiction; San Francisco (Calif.) -- Fiction; China -- Fiction; Domestic fiction; Love stories